Investigation of the Association of Oral Infections with Diabetes Mellitus - Aljubouri, Esraa A.; Alaubydi, Mouruj A. (Iraqi Journal of Science, 2023)
Diabetes mellitus (DM) is a chronic metabolic disease that is considered a major worldwide healthcare problem. Multiple studies have revealed that people with DM are more likely to acquire oral problems, such as periodontal diseases, because the oral microbiota plays a major role in oral health and may affect the saliva composition. This study aimed to characterize the oral microbiota of a sample of DM patients and its association with some demographic factors, such as smoking habits and gender. A total of 91 specimens, including 51 DM patients and 40 apparently healthy individuals, were enrolled in this study, which was carried out from November 2021 to February 2022. Whole saliva was collected in a sterile tube, and oral swabs were obtained from both patients and the control groups. The results of the present study show there was no significant difference between both genders in DM hits. As well, a smoking habit is considered a predisposing habit that may increase the risk of oral diseases in DM patients. The acidic pH of saliva recorded higher values between patients and control subjects than other pH items. On the other hand, the most prevalent bacterial isolates found in oral DM patients were Staphylococcus spp. (37.12%), E.coli (12.9%), Klebsiella  spp. (10.60%), Pseudomonas spp. (9.84%), Enterobacter (8.33%), both Streptococcus spp. and Acinetobacter spp. (5.30%), Corynebacterium spp. and Proteus spp. (3.8%), Neisseria spp. and Haemophilus Influenza was 1.51%. These percentages were significantly different from those in the control group, which were Staphylococcus spp. (43.4%), Klebsiella spp. (25.0%), Enterobacter (7.89%), E.coli (6.58%), Bacillus spp. (5.2%), Acinetobacter spp. (3.9%), Pseudomonas spp., Streptococcus spp., and Proteus spp.  (2.7%).